2021
DOI: 10.1002/ejic.202100137
|View full text |Cite
|
Sign up to set email alerts
|

Structure Effects Induced by High Mechanical Compaction of STAM‐17‐OEt MOF Powders

Abstract: Metal-organic frameworks (MOFs) are promising materials for many potential applications, spacing from gas storage to catalysis. However, the powder form they are generally made of is not suitable, mainly because of the low packing density. Powder compaction is therefore necessary, but also challenging because of its typical mechanical fragility. Indeed, generally, MOF powders undergo irreversibly damages upon densification processes, for example partially or totally loosing microporosity and catalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The calculated Δ H ads are presented in Table . The predicted Δ H ads for CO 2 on a STAM-17-OEt of −19.3 kJ/mol is in reasonable agreement with an experimental isosteric heat of adsorption of −16.2 kJ/mol and at a higher pressure of −27.6 kJ/mol . In the absence of additional experimental data, a definitive conclusion could not be reached for the other gases.…”
Section: Results and Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The calculated Δ H ads are presented in Table . The predicted Δ H ads for CO 2 on a STAM-17-OEt of −19.3 kJ/mol is in reasonable agreement with an experimental isosteric heat of adsorption of −16.2 kJ/mol and at a higher pressure of −27.6 kJ/mol . In the absence of additional experimental data, a definitive conclusion could not be reached for the other gases.…”
Section: Results and Discussionsupporting
confidence: 49%
“…The predicted ΔH ads for CO 2 on a STAM-17-OEt of −19.3 kJ/mol is in reasonable agreement with an experimental isosteric heat of adsorption of −16.2 kJ/mol and at a higher pressure of −27.6 kJ/mol. 55 In the absence of additional experimental data, a definitive conclusion could not be reached for the other gases. However, the calculated ΔH ads still gives us a sense of how STAM-17-OEt will perform under experimental conditions at 298 K.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In particular, the local dynamic metal–carboxylate interactions that underpin whole-framework processes such as ligand/cation exchange have only been reported and rationalized in the MOF literature in recent years. In 2021, we demonstrated that dynamic metal–carboxylate interactions (Figure e) could be exploited to facilitate ammonium uptake in a saturated scandium-based MOF (MFM-300­(Sc)) . This investigation demonstrated an unusual route via which the framework interacts with guest molecules due to the labile Sc­(III)–carboxylate bond interaction present in the MOF architecture.…”
Section: Introductionmentioning
confidence: 82%
“…The concept of hemilability in MOFs and different consequences on the hydrolytic stability and many other properties of this family of porous materials, it has been intensively developed by Morris et al [18][19][20] The associated reversible metal-ligand bond dynamics can explain key phenomena in MOFs from their crystal growth to their phase transitions. [21] For example, Bennett and Horike, elegantly proposed, the different melting mechanisms for ZIFs.…”
Section: Introductionmentioning
confidence: 99%